The Mysterious Hand of (In)Justice: the Thin Line between Crime and Punishment in the Novel “And There Were None” by Agatha Christie (Annual of the Faculty of Philosophy in Skopje, 2017)
This paper aims to contribute to the exploration o f the productive relationshipsbetween philosophy, law and literature, in the spirit o f the contemporary “Law andLiterature " movement. More specifically, it analyses the key leitmotifs o f the famousmystery novel “And Then There Were None" by Agatha Christie, revealing their potential to illustrate the complexity and the deep existential relevance of some o f the mostimportant questions tackled by the philosophy o f law as a discipline. The specific interconnectedness o f the ideas o f justice, guilt, crime, revenge and punishment, reflected bythe complicated structure o f the plot o f Christie's novel, is viewed as an opportunity' totest and further refine our fundamental intuitions about the principles o f justice andtheir practical application.
Keywords: PHILOSOPHY OF LAW; LAW AND LITERATURE; MYSTERY NOVEL; JUSTICE; CRIME; PUNISHMENT